Efeito de extratos aquosos de Cabralea canjerana subsp. polytricha (Adr. Juss.) Penn. (Meliaceae) no controle biológico de Brevycorine brassicae (L.) (Hemiptera: Aphididae) e Ascia monuste orseis (Godart) (Lepidoptera: Pieridae) - Mata, Rosely Ferreira Freitas da (2007)
This work was performed to test the effect of aqueous extract of Cabralea canjerana subsp. polytricha (Meliaceae) in the control of Brevycorine brassicae (Hemiptera: Aphididae) and Ascia monuste orseis (Lepidoptera: Pieridae). Extract of leaves, fruits and seeds of 3, 5 and 10% were obtained through infusion of dry and triturated material in distilled water filtered after 24 hours. The effect of the extracts was tested in the survival of B. brassicae and the viability, larval and pupal weight and repellent/antifeedant activity of A. monuste orseis. Extract of 3 and 5% did not demonstrated insecticide action on B. brassicae. However, extract of 10% of concentration was able to control this insect in laboratory conditions. The larvae of A. monuste orseis demonstrated low viability when treated with leaves immersed in the extracts, dying before completing four days of age, on average. The evaluation of the repellent/antifeedant effect of the extract indicates that, in tests with choice, the individuals tend to avoid leaves treated with seeds extracts. Differences in consumed area were only demonstrated in the tests using extract of 10%. However, cabbage leaves immersed in fruits and seeds extracts presented a lower consumed area. Tests without choice indicate that when extract of 5 and 10% were used, cabbage leaves consumption was reduced.